1890 S.D. Sess. Laws 72, art. 5, &sect - (:unkn) unknown (My University, 1890)
To regulate and prevent the storage of gun powder, tar, pitch, resin, coal, oil, benzine [sic], turpentine, hemp, cotton, nitro-glycerine, petroleum, or any of the products thereof, and other combustible or explosive material, and the use of lights in stables, shops and other places, and the building of bonfires;also to regulate and restrain the use of fire works, fire crackers, torpedoes, roman candles, sky rockets, and other pyrotechnic displays.
1,pt. 53.
Keywords: GUNPOWDER - STORAGE